IMMORTALITAS ORANG SALEH DAN EKSPRESI KEYAKINAN ATAS KONSEP BERKAH - Abdul Najib (UIN Raden Mas Said Surakarta, 2020)
This study aims to discuss the people's understanding of the immortality of pious people in the funeral complex of Lasem Jami’ mosque, and the values embodied in the surrounding community’s daily lives. Based on the phenomenological approach, wherein data is obtained through participant observation and in-depth interviews, the results show that people's belief in immortality is based on their beliefs on the person’s piety, both ritually and socially. It can be seen from the community ways to always put the pious person in an honorable position, through various rituals such as pilgrimage, haul, selametan, and tawasulan. The community beliefs on good deeds will not be broken off after people’s death, becoming their basis to understand in immortality. Immortality can only be obtained by people who can control their bodies and reduce their egos (tazkiyyatun nafs). Immortal pious people are understood to have power and will after their death. This immortal power is believed to be able to provide blessings for the prayers they offered. The ability of the pious people to